2011
DOI: 10.1007/s10661-010-1862-0
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric BTEX concentrations in the vicinity of the crude oil refinery of the Baltic region

Abstract: Among chemical industries, petroleum refineries have been identified as large emitters of a wide variety of pollutants. Benzene, toluene, ethylbenzene, and xylene (BTEX) form an important group of aromatic volatile organic compounds (VOCs) because of their role in the troposphere chemistry and the risk posed to human health. A very large crude oil refinery of the Baltic States (200,000 bbl/day) is situated in the northern, rural part of Lithuania, 10 km from the town of Mažeikiai (Lithuania). The objectives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 38 publications
2
44
1
Order By: Relevance
“…As discussed above, the emission from vehicles was not obvious from the diurnal variation of BTEX and the solvent usage was negligible in the study area. The ratios of m, p-xylenes/ethylbenzene in this study (2.2±1.2) were 30 within the ranges reported at a petrochemical area in southern Taiwan (1.5-2.6) (Hsieh et al, 2006) and the vicinity of a crude oil refinery at the Baltic region (3.0-4.0) (Baltrėnas et al, 2011). Therefore, BTEX in this area was mainly from the oil refinery emission.…”
Section: Ambient Ratios: Sources and Photochemical Removalsupporting
confidence: 84%
See 2 more Smart Citations
“…As discussed above, the emission from vehicles was not obvious from the diurnal variation of BTEX and the solvent usage was negligible in the study area. The ratios of m, p-xylenes/ethylbenzene in this study (2.2±1.2) were 30 within the ranges reported at a petrochemical area in southern Taiwan (1.5-2.6) (Hsieh et al, 2006) and the vicinity of a crude oil refinery at the Baltic region (3.0-4.0) (Baltrėnas et al, 2011). Therefore, BTEX in this area was mainly from the oil refinery emission.…”
Section: Ambient Ratios: Sources and Photochemical Removalsupporting
confidence: 84%
“…The results obtained in this study indicated that there were other factors affecting the seasonal variation, such as source emissions. BTEX mainly originated from vehicle exhaust , solvent usage Yuan et al, 2010) and petrochemical industry (Na and Kim, 2001;Hsieh et al, 2006;Baltrėnas et al, 2011). As discussed above, the emission from vehicles was not obvious from the diurnal variation of BTEX and the solvent usage was negligible in the study area.…”
Section: Ambient Ratios: Sources and Photochemical Removalmentioning
confidence: 84%
See 1 more Smart Citation
“…This was observed in Lithuania, which has a very large crude oil refinery. Benzene concentrations in air in the urban region exceeded the rural region by 0.63 ppb [13]. Air quality at rural regions near these industries was influenced only by the industrial emissions and traffic emissions played a minor role.…”
Section: Volatile Organic Compoundsmentioning
confidence: 95%
“…Regulated emissions and leaks both contribute to the VOCs concentration [12]. Aromatic VOCs are mainly comprised of Benzene, Toluene, Ethylbenzene, and Xylene (BTEX) [13], and benzene is of particular concern since it is carcinogenic. VOCs are associated with a number of potential health effects.…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%